2018
DOI: 10.1002/jcp.27487
|View full text |Cite
|
Sign up to set email alerts
|

DGCR5 attenuates neuropathic pain through sponging miR‐330‐3p and regulating PDCD4 in CCI rat models

Abstract: Neuropathic pain caused by somatosensory nervous system dysfunction is a serious public health problem. Some long noncoding RNAs (lncRNAs) can participate in physiological processes involved in neuropathic pain. However, the effects of lncRNA DGCR5 in neuropathic pain have not been explored. Therefore, in our current study, we concentrated on the biological roles of DGCR5 in neuropathic pain. Here, it was observed that DGCR5 was significantly decreased in chronic sciatic nerve injury (CCI) rat models. DGCR5 ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Elevated PDCD4 expression was observed in the rat spinal cord injury model [33], the chronic sciatic nerve injury (CCI)-induced rat neuropathic pain model [34], the oxygen-glucose deprivation/reoxygenation (OGDR) injury model of rat hippocampal neurons [35], and the ischemia and reperfusion (I/R)-induced neuronal lesion model in mice retinas [25]. The available studies indicate that PDCD4 may be extensively involved in neuronal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated PDCD4 expression was observed in the rat spinal cord injury model [33], the chronic sciatic nerve injury (CCI)-induced rat neuropathic pain model [34], the oxygen-glucose deprivation/reoxygenation (OGDR) injury model of rat hippocampal neurons [35], and the ischemia and reperfusion (I/R)-induced neuronal lesion model in mice retinas [25]. The available studies indicate that PDCD4 may be extensively involved in neuronal damage.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic restraint stress increased PDCD4 expression in mice hippocampus by decreasing the mTORC1-mediated proteasomes degradation [32]. Elevated PDCD4 expression was observed in the rat spinal cord injury model [33], the chronic sciatic nerve injury (CCI)-induced rat neuropathic pain model [34], the oxygen-glucose deprivation/reoxygenation (OGDR) injury model of rat hippocampal neurons [35], and the ischemia and reperfusion (I/R)-induced neuronal lesion model in mouse retina [25]. The available studies have indicated that PDCD4 may be extensively involved in neuronal damage.…”
Section: Discussionmentioning
confidence: 99%
“…They relieved hyperalgesia and decreased neuroinflammation by modulating the P2X 3 receptor or P2X 7 receptor. In addition to the lncRNAs reported above, some lncRNAs have also been reported to be associated with NP [19,[120][121][122][123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138].…”
Section: Lncrnas and Npmentioning
confidence: 99%
“…Compared with sham CCI, the lncRNA DGCR5 was downregulated in the spinal cord of CCI rats. DGCR5 could negatively regulate the expression of miR-330-3p and suppress neuroinflammation and hyperalgesia by sponging miR-330-3p and modulating the downstream target PDCD4 [134]. Dou and colleagues [136] showed that the lncRNA CCAT1 was significantly decreased in the DRG, spinal cord, hippocampus, and anterior cingulate cortex of CCI rats.…”
Section: Interactions Among Lncrnas Mirnas and Mrnas In Npmentioning
confidence: 99%